Relative multi-beneficial effect of MOs on plant health of chickpea (Cicer arietinum L. var. PG-186) - Tomer, Supriya; Khati, Priyanka; Suyal, Deep Chandra; Perveen, Kahkashan; Khan, Faheema; Barasarathi, Jayanthi (Frontiers in Microbiology, 2024)
The phosphate solubilizing properties of Lysinibacillus macroides ST-30, Pseudomonas pelleroniana N-26, Bacillus cereus ST-6 were tested for chickpea crop of Tarai region of Uttarakhand. These microbial inoculants treated plants have shown significant (P> 0.05) improvement in the plant health and crop health parameters viz. root length, shoot length, fresh weight, dry weight, nodule number, nodule fresh weight, nodule dry weight and chlorophyll content, nitrate reductase. Highest shoot length (46.10 cm) and chlorophyll content (.57 mg g-1 fresh weight) was observed in ST-30 at 75 DAS with 20 Kg P2O5/ha. Similarly for plant P content an increase of 90.12 % percentage over control was recorded in same treatment. A significant increase in plant P contents of treatments containing microbial inoculants was observed. Treatments consisting Lysinibacillus macroides ST-30 along with 20 kg/ha P2O5 were found most suitable as phosphatic fertilizer. Conclusively, the sustainable agriculture practice in the Tarai as well as field region may be developed on a strategy of exploring microbial inoculants from the pristine region Western Himalayas. The presence and abundance of bacterial inoculants was confirmed through qRT-PCT. We conclude that the effective plant growth-promoting bacterium Lysinibacillus macroides ST-30 broadens the spectrum of phosphate solubilizers available for field applications and might be used together with 20 Kg/ha P2O5.